The structure of a cypovirus and the functional organization of dsRNA viruses. - Hill, C; Booth, T; Prasad, B; Grimes, J; Mertens, P; Sutton, G; Stuart, D (1999)
Cytoplasmic polyhedrosis virus (CPV) is unique among the double-stranded RNA viruses of the family Reoviridae in having a single capsid layer. Analysis by cryo-electron microscopy allows comparison of the single shelled CPV and orthoreovirus with the high resolution crystal structure of the inner shell of the bluetongue virus (BTV) core. This suggests that the novel arrangement identified in BTV, of 120 protein subunits in a so-called 'T=2' organization, is a characteristic of the Reoviridae and allows us to delineate structural similarities and differences between two subgroups of the family--the turreted and the smooth-core viruses. This in turn suggests a coherent picture of the structural organization of many dsRNA viruses.